4(3a-1)=10-(a+3)

Simple and best practice solution for 4(3a-1)=10-(a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3a-1)=10-(a+3) equation:


Simplifying
4(3a + -1) = 10 + -1(a + 3)

Reorder the terms:
4(-1 + 3a) = 10 + -1(a + 3)
(-1 * 4 + 3a * 4) = 10 + -1(a + 3)
(-4 + 12a) = 10 + -1(a + 3)

Reorder the terms:
-4 + 12a = 10 + -1(3 + a)
-4 + 12a = 10 + (3 * -1 + a * -1)
-4 + 12a = 10 + (-3 + -1a)

Combine like terms: 10 + -3 = 7
-4 + 12a = 7 + -1a

Solving
-4 + 12a = 7 + -1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'a' to each side of the equation.
-4 + 12a + a = 7 + -1a + a

Combine like terms: 12a + a = 13a
-4 + 13a = 7 + -1a + a

Combine like terms: -1a + a = 0
-4 + 13a = 7 + 0
-4 + 13a = 7

Add '4' to each side of the equation.
-4 + 4 + 13a = 7 + 4

Combine like terms: -4 + 4 = 0
0 + 13a = 7 + 4
13a = 7 + 4

Combine like terms: 7 + 4 = 11
13a = 11

Divide each side by '13'.
a = 0.8461538462

Simplifying
a = 0.8461538462

See similar equations:

| -24+h=-45 | | 3(x-4)-8=2x | | 3(1-2y)=8-3y | | 5+6y=y+20 | | 5(2a+7)=5(4-a) | | 5(x-2)=3x-12 | | 1=x+1/16 | | -12-66=-9x+21 | | 4a+6=2a+20 | | 10(x-3)=5(x+5) | | 41+6=2a+20 | | 3x-(6+2x)=22 | | -83=4r-7 | | 5(y+4)=3y+6 | | 1.16y-6=8 | | -5x-22=38-2x | | x+6x-3-2x=27 | | 1+n=-3 | | -4(a+6)+14=10 | | 2(5y+3)=46 | | 3x-45=24+6x | | -72=18x | | 36x^2+9y^2=81 | | -12x-82=74-6x | | -30=v-10 | | 51=-3a | | -7x-162=9x+46 | | 5(m+3)=2(3m+1) | | (94)=136 | | 3x^2-x+7=0 | | -91-9x=-3x+35 | | -112+128x-16x^2=0 |

Equations solver categories